2013
DOI: 10.1016/j.surg.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel pharmacologic treatment attenuates septic shock and improves long-term survival

Abstract: Background We have previously demonstrated that suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor, improves survival in a lipopolysaccharide (LPS)-induced lethal endotoxemia model. The goal of this study was to investigate the impact of SAHA on survival in a more clinically relevant cecal ligation and puncture (CLP)-induced septic shock model, and to elucidate changes in cytokine responses and organ injury. Methods C57BL/6J mice were subjected to CLP, and 1 hour later given either SAHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…Our research team has demonstrated that both hemorrhage and sepsis can lead to protein hypoacetylation, whereas therapeutically targeting the alterations with HDACIs induces acetylation of histone and non-histone proteins, and is protective against lethal insults, such as hemorrhagic shock, traumatic brain injuries, endotoxemic shock, and severe sepsis. 15-18 In humans and mice, the 18 HDAC enzymes are grouped into four classes: classical HDACs, including class I, II and IV, are Zn 2+ dependent, while the classes III sirtuins act through a NAD + -dependent mechanism. HDAC6 belongs to class IIb HDAC and is unique in that it is a cytoplasmic microtubule-associated enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team has demonstrated that both hemorrhage and sepsis can lead to protein hypoacetylation, whereas therapeutically targeting the alterations with HDACIs induces acetylation of histone and non-histone proteins, and is protective against lethal insults, such as hemorrhagic shock, traumatic brain injuries, endotoxemic shock, and severe sepsis. 15-18 In humans and mice, the 18 HDAC enzymes are grouped into four classes: classical HDACs, including class I, II and IV, are Zn 2+ dependent, while the classes III sirtuins act through a NAD + -dependent mechanism. HDAC6 belongs to class IIb HDAC and is unique in that it is a cytoplasmic microtubule-associated enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that an HDACI, suberoylanilide hydroxamic acid (SAHA), modulates the immune response, 79 and improves survival in a mouse model of cecal ligation and puncture (CLP). 10 Unfortunately, this non-selective HDAC inhibitor is not well tolerated, and may impair the innate immune response when given in therapeutically relevant doses. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Our lab was the first to demonstrate that administration of suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor (HDACI), improved survival in lethal rodent models of lipopolysaccharide (LPS)-induced endotoxemia and cecal ligation and puncture (CLP)-induced severe sepsis 810 . Selective inhibition of HDAC6 with Tubastatin A displays even better survival outcomes in the lethal CLP-sepsis model and increases bacterial clearance in circulation (unpublished data).…”
Section: Introductionmentioning
confidence: 99%